PERSIAPAN KOMPETISI SAINS NASIONAL (KSN) 2020 MELALUI BIMBINGAN BELAJAR DI SD NEGERI 1 LAMOKATO KABUPATEN KOLAKA - Ernawati Ernawati; Tri Maniarta Sari; A.S. Alonemarera; Fitriani Abdul Asis; Dina Nurhayati (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
The National Science Olympiad (OSN), which in 2020 changed its name to the National Science Competition (KSN), is held in stages to motivate students, teachers, managers and education coaches to compete healthily in order to improve the quality of national education. In the field of science, in previous years the results in Kolaka Regency were still in the low category, including SDN 1 Lamokato. In the academic year 2019/2020 SD Negeri 1 Lamokato will send again its students to take part in the 2020 KSN.Therefore, there needs to be preparation early, one of the preparation iswith the Community Service program by a team of lecturers and students of the Biology Education Study Program, Sembilanbelas November Kolaka University. which was carried out in the form of providing learning guidance for KSN-SD preparation. PkM activities include the stages of preparation, implementation and evaluation. The preparation stage includes curriculum analysis and OSN questions and giving pretest questions. The implementation stage includes the provision of material about OSN, guidance and assistance in solving OSN questions, and the evaluation stage includes giving posttest questions and questionnaires at the end of the activity. The results of the implementation of PkM tutoring for the National Science Competition (KSN-SD) at SD Negeri 1 Lamokato went smoothly and had a positive impact on the preparation for the KSN-SD students in 2020. This result was shown by the increased ability of participants to solve Olympic questions (from scores the average pretest 45.83 to 75.0 at posttest). The results of the evaluation questionnaire analysis also showed that the participants were motivated (83.33%), the participants' understanding of the material and the supervisor's ability to provide the material was considered very good (88.89%). However, additional time is needed in mentoring and mentoring participants who will take part in the KSN-SD selection so that this activity can provide an optimal contribution. Keywords: KSN-SD 2020; Science tutoring.